ELECTRONIC WORD OF MOUTH (E-WOM) ON PURCHASE DECISIONS MEDIATED BY BRAND TRUST (STUDY ON WARDAH CONSUMERS IN JAYAPURA) - Lestari, Rini Ayu (Scientia integritas Utama, 2022)
The purpose of this research is to examine an empirical evidence in the form of Electronic Word Of Mouth (e-WOM) variables on Purchase Decisions mediated by Brand Trust. This study's sample consisted of all consumers of Wardah brand cosmetics in Jayapura. Sampling in the study used Probability Sampling, research data were obtained utilizing a questionnaire distributed online via Google form as a study instrument to respondents containing 13 statement items as measured using an interval scale. The data analysis method used in this study is Structual Equation Modeling (SEM). The results of the study show empirical evidence that Brand Trust significantly mediates Electronic Word Of Mouth (e-WOM) on Purchasing Decisions. The contribution of the results of this study can obtain empirical evidence regarding the factors that influence purchasing decisions, which can provide information to the holders of the Wardah cosmetic brand so that they can maintain quality and improve the quality of Wardah brand products.